Silicon-based negative electrode active material, negative electrode sheet and lithium-ion battery

By setting an ion adsorption layer and a conductive layer in the silicon-based negative electrode active material, the problem of lithium-ion battery extrusion and cyclic expansion under large-scale fast charging is solved, and better lithium-ion window and cyclic performance are achieved.

CN115483389BActive Publication Date: 2025-02-14HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211131301.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-02-14
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the electron and ion conduction capacity of silicon materials is poor, making it difficult to meet the large-scale fast charging, and the problem of lithium evolution causing cycle failure is prone to occur under large-scale fast charging.

Method used

Design a silicon-based negative electrode active material, including a silicon-based core, an ion adsorption layer coated on the surface of the silicon-based core, and a conductive layer coated on the outer surface of the ion adsorption layer, and is controlled by the thickness and proportion of the ion adsorption layer and the conductive layer. , balances electron conduction and ion conduction in batteries.

Benefits of technology

By setting up an ion adsorption layer and a conductive layer, the fast charging capability of the silicon negative electrode material is improved, the lithium-ion window is maintained, the expansion rate of the battery is reduced, and the circulation performance of the lithium-ion battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115483389B_ABST
    Figure CN115483389B_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon-based negative electrode active material, a negative electrode sheet and a lithium ion battery. The silicon-based negative electrode active material comprises a silicon-based core and an ion adsorption layer and a conductive layer sequentially coated on the surface of the silicon-based core; the thickness of the ion adsorption layer and the conductive layer are 50-500nm and 20-200nm respectively, and the ratio of the thickness of the two is greater than or equal to 2. Among them, the ion adsorption layer is arranged between the silicon-based core and the conductive layer, and the lithium ions gathered on the surface of the material can be absorbed into the ion adsorption layer, the ion enrichment on the surface of the negative electrode silicon-based material is reduced, the precipitation of lithium ions on the surface of the negative electrode sheet is alleviated, and the expansion pressure of the silicon-based core can be alleviated, and the overall material structure stability can be improved; by controlling the thickness and thickness ratio of the ion adsorption layer and the conductive layer, the electronic conduction and ion conduction in the battery can be balanced, so that lithium ions can be easily embedded in the material and lithium can be slowly decomposed, and then the silicon-based negative electrode active material can improve the lithium precipitation window and cycle performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a silicon-based negative electrode active material, a negative electrode sheet and a lithium ion battery. Background Art

[0002] In the existing secondary battery system, lithium-ion batteries are widely used in digital products and power supplies due to their advantages such as high operating voltage, large specific capacity, stable discharge, small size, light weight, and green environmental protection. However, with the continuous development of technology, higher requirements are placed on lithium-ion batteries. As an important factor affecting the performance of lithium-ion batteries, negative electrode materials have also been subject to more and more extensive research.

[0003] Graphite material has the advantages of small volume expansion coefficient and high coulomb efficiency during the battery charging and discharging process. It is currently the most widely used negative electrode material for lithium-ion batteries. However, its maximum theoretical capacity is relatively low (only 372mAh / g), which limits the development of lithium-ion batteries. Among non-carbon negative electrode materials, silicon material has a high theoretical lithium insertion capacity (4200mAh / g), which is about 10 times that of commercial graphite negative electrode. It is a more promising negative electrode material and is increasingly used in commercial lithium-ion batteries. However, silicon materials have poor electronic and ion conductivity, and have encountered great challenges in the field of fast charging. It is difficult to meet the requirements of high-rate fast charging. Under high-rate fast charging, lithium plating is prone to occur, leading to cycle failure. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a silicon-based negative electrode active material, a negative electrode sheet and a lithium ion battery.

[0005] In a first aspect of the present invention, a silicon-based negative electrode active material is provided, comprising:

[0006] Silicon-based core;

[0007] An ion adsorption layer, coated on the surface of the silicon-based core, wherein the thickness of the ion adsorption layer is 50 to 500 nm;

[0008] A conductive layer is coated on the surface of the ion adsorption layer away from the silicon-based core, the thickness of the conductive layer is 20 to 200 nm, and the ratio of the thickness of the ion adsorption layer to the conductive layer is greater than or equal to 2.

[0009] According to the silicon-based negative electrode active material of the embodiment of the present invention, at least the following beneficial effects are achieved: the outer surface of the silicon-based core in the silicon-based negative electrode active material is coated with an ion adsorption layer, and the surface of the ion adsorption layer is coated with a conductive layer. Among them, by coating the surface of the silicon-based core with an ion adsorption layer, on the one hand, the ions gathered on the surface of the material can be absorbed into the ion adsorption layer, reducing the surface enrichment of ions on the negative electrode silicon-based material, alleviating the precipitation of lithium ions on the surface of the negative electrode sheet, thereby improving the fast charging ability of the silicon negative electrode material, so that it can still maintain a good lithium precipitation window at a high rate, and on the other hand, it can also prevent the silicon-based core from contacting with the electrolyte to produce side reactions. At the same time, the setting of the ion adsorption layer can produce a certain binding strength to relieve the pressure of silicon expansion, so that the overall material structure remains stable, and thus the expansion rate of the battery can be reduced; and the outer surface of the ion adsorption layer is further coated with a conductive layer to improve the electronic conduction capacity. In addition, since the ion adsorption layer affects the amount and rate of lithium ion absorption, if the ion adsorption layer is too thick, the lithium ions will exist in the ion adsorption layer after adsorption and cannot be well embedded in the silicon-based core. If it is too thin, the amount of lithium ions absorbed is too small and the adsorption effect cannot be achieved. The conductive layer can conduct electrons. If the conductive layer is too thin, the electron transfer is slow, which is not conducive to the formation of electric potential, and if it is too thick, it will hinder the passage of ions. Therefore, by controlling the thickness and ratio of the ion adsorption layer and the conductive layer, the electronic conduction and ion conduction in the battery can be balanced, so that lithium ions can be easily embedded in the material and the occurrence of lithium desorption can be slowed down. Therefore, through the above settings, the silicon-based negative electrode active material can improve the lithium desorption window and cycle performance of lithium-ion batteries.

[0010] In some embodiments of the present invention, the material of the ion adsorption layer is selected from at least one of nanocellulose, nanocellulose derivatives, and metal organic framework nanocomposites. The metal contained in the metal organic framework nanocomposites may be at least one of aluminum, iron, copper, chromium, zinc, and zirconium.

[0011] In some embodiments of the present invention, the nanocellulose derivative includes at least one of nano-esterified cellulose, nano-etherified cellulose and other nano-grafted cellulose. Among them, the nano-esterified cellulose can be cellulose nitrate, cellulose xanthate, cellulose sulfate or other organic cellulose esters; the nano-etherified cellulose can be carboxymethyl cellulose, methyl cellulose, carboxyethyl cellulose or other cellulose ethers; the nano-grafted cellulose can be acrylic cellulose, acrylamide cellulose, ethylenediamine cellulose, succinic anhydride cellulose, hydroxylamine cellulose, acrylonitrile cellulose, etc.

[0012] In some embodiments of the present invention, the silicon-based core is selected from at least one of silicon-oxygen particles, pre-treated silicon-oxygen particles, silicon nanowires, and silicon-carbon particles.

[0013] The silicon-based active material is prepared by using the silicon-based material as the core, and then used in the preparation of the negative electrode sheet of the lithium-ion battery, which can improve the energy density of the battery system. In some embodiments of the present invention, the conductive layer is made of residual carbon.

[0014] In some embodiments of the present invention, the thickness of the ion adsorption layer is 200-500 nm; preferably, the thickness of the conductive layer is 50-100 nm.

[0015] In some embodiments of the present invention, the ratio of the thickness of the ion adsorption layer to the thickness of the conductive layer is greater than or equal to 3; preferably, the ratio of the thickness of the ion adsorption layer to the thickness of the conductive layer is greater than or equal to 4 and less than or equal to 6.

[0016] The present application does not limit the specific preparation method of the above silicon-based negative electrode active material, and the above method can be achieved by coating the ion adsorption layer on the surface of the silicon-based core, and coating the conductive layer on the surface of the ion adsorption layer. For example, the ion adsorption layer can be coated on the surface of the silicon-based core in the following manner: specifically, an ion adsorption material solution can be prepared first, and then the silicon-based core can be dispersed in the ion adsorption material solution to obtain a dispersion, and then dried to solidify the ion adsorption material and coat it on the surface of the silicon-based core to form an ion adsorption layer; the thickness of the ion adsorption layer can be controlled by controlling the concentration of the ion adsorption material solution. For example, nanocellulose can be dissolved in water, and then a small amount of NaClO and NaOH are added to control the pH value to prepare a modified nanocellulose solution, and then the silicon-based core is dispersed in a modified nanocellulose solution containing a specific concentration to obtain a dispersion, and then dried at high temperature, and the nanocellulose derivative is solidified on the surface of the silicon-based core to obtain an ion adsorption layer; wherein, the ion adsorption layer can be controlled by controlling the concentration of modified nanocellulose in the modified nanocellulose solution to control the coating thickness, similar to using a modified nanocellulose solution with a concentration of 0.5wt% to prepare an ion adsorption layer with a thickness of 200nm, using a modified nanocellulose solution with a concentration of 0.25wt% to prepare an ion adsorption layer with a thickness of 100nm, and using a modified nanocellulose solution with a concentration of 0.75wt% to prepare an ion adsorption layer with a thickness of 300nm. In addition, a conductive layer can be coated on the surface of the ion adsorption layer by vapor deposition, for example, an alkane can be used to prepare a conductive layer on the surface of the ion adsorption layer by vapor deposition at 800-900°C, wherein the thickness of the conductive layer can be controlled by the flow rate of the alkane and the vapor deposition temperature.

[0017] In the second aspect of the present invention, a negative electrode sheet is proposed, comprising a negative electrode current collector and a negative electrode active material layer coated on the surface of the negative electrode current collector, wherein the preparation material of the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises any one of the silicon-based negative electrode active materials proposed in the first aspect of the present invention.

[0018] In some embodiments of the present invention, the silicon-based negative electrode active material accounts for 3 to 20% of the total mass of the negative electrode active material; preferably, the silicon-based negative electrode active material accounts for 3 to 10% of the total mass of the negative electrode active material; further preferably, the silicon-based negative electrode active material accounts for 3 to 7% of the total mass of the negative electrode active material.

[0019] The third aspect of the present invention provides a lithium ion battery, which includes the negative electrode sheet provided in the second aspect of the present invention. The lithium ion battery may specifically include a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet.

[0020] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer covering the surface of the positive electrode current collector. The material of the positive electrode active material layer may include a positive electrode active material, a conductive agent and a binder. The positive electrode active material may be LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiMnPO4, LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.1 Mn 0.3 O2、LiNi 0.85 Co 0.15 Al 0.05 The separator may be one or more composite films of polyethylene, polypropylene, polyvinylidene fluoride, but is not limited thereto, and may also be other separators. The electrolyte may include electrolyte salts and organic solvents, wherein the specific types and compositions of the electrolyte salts and organic solvents are not limited, and conventional electrolyte salts and organic solvents that constitute the electrolyte of lithium-ion batteries may be used. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0022] Figure 1 Schematic diagram of the structure of the silicon-based negative electrode active material in Example 1. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0024] Example 1

[0025] This embodiment prepares a lithium ion battery, and the preparation method thereof is as follows:

[0026] S1. Preparation of positive electrode sheets, including: fully dispersing positive electrode active material LiCoO2, conductive agent acetylene black, conductive carbon nanotubes, and binder polyvinylidene fluoride (PVDF) in a weight ratio of 98.2:0.5:0.3:1.0 in an N-methylpyrrolidone solvent system to prepare a positive electrode active slurry with a solid content of 75%; then uniformly coating it on a 9um thick aluminum current collector with a coating thickness of about 45μm, and then cold pressing and slitting to obtain positive electrode sheets;

[0027] S2. Preparation of negative electrode sheets, including: mixing negative electrode active materials, conductive agents and binders in a mass ratio of 97.2:0.5:2.3 in a solvent to prepare a negative electrode active slurry with a solid content of 50%, and then coating it on a copper current collector with a thickness of 5μm, with a coating thickness of about 45μm, and then cold pressing and slitting to obtain negative electrode sheets. Among them, the conductive agent is selected from conductive carbon black (SP) and carbon nanotubes (CNT) with a mass ratio of 0.45:0.05; the binder is selected from styrene-butadiene rubber (SBR) and polyacrylate lithium (PAALi) with a mass ratio of 0.5:1.8; the negative electrode active material includes 97wt% graphite and 3wt% silicon-based active materials, and the structure of the silicon-based active materials is as follows Figure 1 As shown, it specifically includes a silicon-based core 11, an ion adsorption layer 12 coated on the surface of the silicon-based core 11, and a conductive layer 13 coated on the outer surface of the ion adsorption layer 12; the silicon-based core 11 is specifically a silicon oxide material; the material of the ion adsorption layer 12 is nano methyl acrylate cellulose, and the thickness of the ion adsorption layer 12 is 200nm; the material of the conductive layer 13 is residual carbon, and the thickness of the conductive layer 13 is 50nm.

[0028] S3, preparation of electrolyte: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4 to prepare a mixed organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte;

[0029] S4. Coat the surface of the PE diaphragm with a ceramic mixture as a diaphragm, wind the positive electrode sheet, diaphragm, and negative electrode sheet into a bare battery cell, and then package and inject electrolyte to obtain a lithium-ion battery.

[0030] The lithium ion batteries of Examples 2 to 15 and Comparative Examples 1 to 10 were prepared in a similar manner to the preparation method of the lithium ion battery of Example 1, the main difference from Example 1 being the preparation of the negative electrode sheet, and the other operations were the same as Example 1. The design parameters of the negative electrode sheet in the lithium ion batteries of each Example and Comparative Example are shown in Table 1 below.

[0031] Table 1

[0032]

[0033]

[0034] Performance Testing

[0035] The performance tests of the lithium-ion batteries prepared in the above embodiments and comparative examples were respectively carried out, specifically including:

[0036] (1) Capacity retention test

[0037] The specific test method is: charge the lithium-ion battery in steps from 2.6C to 4.2C, charge at a rate of 1.8C to a cut-off voltage of 4.48V, measure the percentage of the remaining capacity after 800 cycles to the initial capacity, and obtain the capacity retention rate.

[0038] (2) Cycle expansion rate

[0039] The specific test method is: charge the lithium-ion battery in steps from 2.6C to 4.2C, charge at a rate of 1.8C to a cut-off voltage of 4.48V, use a 600g PPG thickness gauge to measure the initial full thickness L1 of the lithium-ion battery, and the final full thickness L2 of the lithium-ion battery after 800 cycles, then the cycle expansion rate = L1 / L2.

[0040] (3) Lithium deposition window test

[0041] Specifically, the lithium-ion battery is charged to 4.2V at 2.0C, 2.2C, 2.4C, 2.6C, 2.8C, 3.0C, and 3.2C stages, and charged to a cut-off voltage of 4.48V at a rate of 1.5C. The maximum charge rate is taken when there is no lithium deposition after 20 cycles.

[0042] The capacity attenuation rate, cycle expansion rate and lithium precipitation window of the lithium ion batteries prepared in each embodiment and comparative example were tested according to the above method, and the results are shown in Table 2.

[0043] Table 2

[0044] Lithium-ion battery Capacity retention rate / % Cycle expansion rate / % Lithium Separation Window Example 1 85% 9.2% 3.0C Example 2 85% 7.8% 3.2C Example 3 81% 9.8% 2.6C Example 4 84% 8.0% 3.2C Example 5 82% 9.6% 2.6C Example 6 83% 8.2% 3.2C Example 7 86% 8.3% 3.2C Comparative Example 1 78% 11.2% 2.4C Comparative Example 2 76% 12.5% 2.0C Comparative Example 3 77% 13.8% 2.0C Example 8 87% 7.6% 3.3C Example 9 73.0% 12.0% 2.0C Example 10 70.0% 14.6% 1.8C Comparative Example 4 65.0% 16.1% 1.5C Comparative Example 5 40.0% 18.7% 1.0C Comparative Example 6 30.0% 20.3% 0.7C Embodiment 11 82% 9.5% 2.8C Example 12 83% 9.3% 2.9C Example 13 84% 9.1% 3.0C Embodiment 14 86% 8.8% 3.2C Embodiment 15 85% 9.3% 3.0C Comparative Example 7 76% 12.2% 2.2C Comparative Example 8 78% 11.5% 2.3C Comparative Example 9 77% 11.8% 2.0C Comparative Example 10 76% 12.2% 2.0C

[0045] According to Tables 1 and 2 above, by comparing the lithium ion batteries of Examples 1 to 15 (especially Examples 2, 9, and 10) and Comparative Examples 2 to 3, 5 to 6 and their performance test results, it can be seen that compared with Comparative Examples 2 and 3 and Comparative Examples 5 and 6, the silicon-based negative electrode active material added to the negative electrode active material layer on the negative electrode sheet of the lithium ion batteries does not contain an ion adsorption layer between the silicon-based core and the surface conductive layer. In the lithium ion batteries of Examples 1 to 15, a silicon-based negative electrode active material consisting of a silicon-based core, an ion adsorption layer coated on the surface of the silicon-based core, and a conductive layer coated on the outer surface of the ion adsorption layer is added to the negative electrode active material layer on the negative electrode sheet. The lithium ion battery has a larger residual capacity after cycling, a smaller capacity loss, a smaller expansion rate after cycling, and a higher lithium precipitation window. It can be seen that the provision of an ion adsorption layer between the silicon-based core and the surface conductive layer in the silicon-based negative electrode active material can improve the lithium precipitation window and cycle performance of the lithium ion battery.

[0046] By comparing the lithium ion batteries of Examples 1, 2, 11 to 15 and Comparative Examples 1, 7 to 10 and their performance test results, it can be seen that the thickness of the ion adsorption layer and the conductive layer of the silicon-based negative electrode active material in the negative electrode active material layer and the thickness ratio of the two will affect the performance of the lithium ion battery. The thickness of the ion adsorption layer of the silicon-based negative electrode active material in the negative electrode active material layer on the negative electrode sheet of the lithium ion batteries of Examples 1 to 2, 11 to 15 is controlled at 50 to 500 nm, the thickness of the conductive layer is controlled at 20 to 200 nm, and the ratio of the thickness of the ion adsorption layer to the conductive layer is greater than or equal to 2. Compared with the lithium ion batteries of Comparative Examples 1, 7 to 10, the thickness of the ion adsorption layer and the conductive layer of the silicon-based negative electrode active material on the negative electrode sheet is not controlled within the above range. The residual capacity of the lithium ion batteries of Examples 1 to 2, 11 to 15 after cycling is larger, the expansion rate is smaller, and the lithium precipitation window is higher.

[0047] By comparing the lithium ion batteries of Examples 2, 3, 9, 10 and Comparative Examples 4 to 6 and their performance test results, it can be seen that on the basis of adding a silicon-based negative electrode active material composed of a silicon-based core and an ion adsorption layer and a conductive layer sequentially coated on its surface to the negative electrode active material, its usage ratio also has a significant effect on the performance of the lithium ion battery, wherein the mass ratio of the silicon-based negative electrode active material in the negative electrode active material of the negative electrode active material layer on the negative electrode sheet is generally controlled at 3wt% to 20wt%, and within this range, the increase in the content of the silicon-based negative electrode active material will deteriorate the lithium precipitation window and cycle of the lithium ion battery. Since silicon is a semiconductor material, its lithium insertion speed is very slow. If lithium ions cannot be embedded in time, they will be precipitated on the surface of the pole piece, resulting in rapid capacity decay and expansion failure. However, providing an ion adsorption layer between the silicon-based core and the outer surface conductive layer of the silicon-based negative electrode active material will compensate and improve the above shortcomings to a certain extent. After the ion adsorption layer is added, the ions no longer exist on the surface, but can be stored in the adsorption layer, so that they will not be precipitated on the surface, thereby improving the lithium precipitation window and cycle performance of the lithium ion battery. Specifically, by comparing the performance test results of lithium-ion batteries in Examples 2, 3, 9, 10 and Comparative Example 4, it can be seen that if the mass proportion of silicon-based negative electrode active material in the negative electrode active material of the negative electrode active material layer on the negative electrode sheet exceeds 20wt%, the use of the above silicon-based negative electrode active material cannot solve the problems of lithium precipitation and cycle expansion; by comparing the performance test results of lithium-ion batteries in Examples 2, 3, 9, 10 and Comparative Examples 5 and 6, it can be seen that the mass proportion of silicon-based negative electrode active material in the negative electrode active material of the negative electrode active material layer on the negative electrode sheet is controlled within 10wt%. In the range of % to 20wt%, a lithium ion adsorption layer is arranged between the silicon-based core and the outer surface conductive layer of the silicon-based negative electrode active material, which can still greatly improve the cycle performance and lithium precipitation window of the lithium ion battery. However, according to the performance test results of the lithium ion batteries in Examples 1 to 10 (especially Examples 2, 3, 9, and 10), it can be seen that the proportion of silicon-based negative electrode active material in the negative electrode active material of the negative electrode active material layer on the negative electrode sheet is preferably controlled in the range of 3wt% to 10wt%, and further preferably controlled in the range of 3wt% to 7wt%.

[0048] From the above, the silicon-based negative electrode active material of the present application can absorb the ions gathered on the surface of the material into the ion adsorption layer by coating the surface of the silicon-based core with an ion adsorption layer, reduce the surface enrichment of ions on the negative electrode silicon-based material, and alleviate the precipitation of lithium ions on the negative electrode surface, thereby improving the fast charging ability of the silicon negative electrode material, so that it can still maintain a good lithium precipitation window at a high rate; on the other hand, it can prevent the silicon-based core from contacting with the electrolyte to produce side reactions. At the same time, the setting of the ion adsorption layer can produce a certain binding strength to alleviate the pressure of the silicon-based core expansion, so that the entire material structure remains stable and the cycle expansion rate of the lithium-ion battery is reduced. By further coating the outer surface of the ion adsorption layer with a conductive layer, the electronic conductivity can be improved. Since the ion adsorption layer affects the absorption amount and rate of lithium ions, if the ion adsorption layer is too thick, the lithium ions will exist in the ion adsorption layer after adsorption and cannot be well embedded in the silicon-based core. If it is too thin, the amount of lithium ions absorbed is too small and the adsorption effect cannot be achieved. The conductive layer can conduct electrons. If it is too thin, the electron transfer is slow, which is not conducive to the formation of electric potential, and if it is too thick, it will hinder the passage of ions. Therefore, by controlling the thickness of the ion adsorption layer and the conductive layer to 50-500nm and 20-200nm respectively, and controlling the thickness ratio of the ion adsorption layer to the conductive layer to be greater than or equal to 2, the electronic conduction and ion conduction in the battery can be balanced, so that lithium ions can be easily embedded in the material and the occurrence of lithium desorption can be slowed down. Therefore, through the above settings, the silicon-based negative electrode active material can improve the lithium desorption window and cycle performance of lithium-ion batteries.

[0049] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A silicon-based negative electrode active material, characterized in that: include: Silicon-based core; An ion adsorption layer is coated on the surface of the silicon-based core, and the thickness of the ion adsorption layer is 50 to 500 nm; the material of the ion adsorption layer is selected from at least one of nanocellulose, nanocellulose derivatives, and metal organic framework nanocomposites; A conductive layer is coated on the surface of the ion adsorption layer away from the silicon-based core, the thickness of the conductive layer is 20 to 200 nm, and the ratio of the thickness of the ion adsorption layer to the conductive layer is greater than or equal to 2.

2. The silicon-based negative electrode active material according to claim 1, characterized in that: The nanocellulose derivative includes at least one of nano-esterified cellulose and nano-etherified cellulose.

3. The silicon-based negative electrode active material according to claim 1, characterized in that: The silicon-based core is selected from at least one of silicon-oxygen particles, pre-treated silicon-oxygen particles, silicon nanowires, and silicon-carbon particles.

4. The silicon-based negative electrode active material according to claim 1, characterized in that: The conductive layer is made of carbon residue.

5. The silicon-based negative electrode active material according to claim 1, characterized in that: The thickness of the ion adsorption layer is 200-500 nm.

6. The silicon-based negative electrode active material according to claim 5, characterized in that: The thickness of the conductive layer is 50-100 nm.

7. The silicon-based negative electrode active material according to any one of claims 1 to 6, characterized in that: A ratio of the thickness of the ion adsorption layer to the thickness of the conductive layer is greater than or equal to 3.

8. The silicon-based negative electrode active material according to claim 7, characterized in that: The ratio of the thickness of the ion adsorption layer to the thickness of the conductive layer is greater than or equal to 4 and less than or equal to 6.

9. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer coated on the surface of the negative electrode current collector, wherein the preparation material of the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises the silicon-based negative electrode active material according to any one of claims 1 to 8.

10. The negative electrode sheet according to claim 9, characterized in that: The silicon-based negative electrode active material accounts for 3-20% of the total mass of the negative electrode active material.

11. The negative electrode sheet according to claim 10, characterized in that: The silicon-based negative electrode active material accounts for 3-10% of the total mass of the negative electrode active material.

12. A lithium ion battery, characterized in that: A negative electrode sheet comprising any one of claims 9 to 11.

Citation Information

Patent Citations

  • Silicon composite negative electrode material and preparation method thereof, and secondary battery

    CN113964303A